Multi-domain united link adaptation technique in high-throughput satellite communication system. (1st March 2023) - Liu, Haike; You, Yang; Shi, Lifeng; Zhang, Huajiian
Abstract: Under the condition of using the same frequency resources, the communication capacity of high-throughput satellites is tens or even hundreds of times higher than that of traditional satellites. Compared with traditional satellites, high-throughput satellites have a large capacity, high speed, and anti-interference characteristics. However, the high-throughput satellite communication link using Ku/Ka-band is vulnerable to weather factors such as rain attenuation, so the system should have a control mechanism to achieve fade countermeasures. The existing methods include transmission power adjustment, mod cod adaptive adjustment, carrier symbol rate adjustment, etc. In this paper, various technical means are comprehensively used to compare and analyze the effect of combined control and propose a multi-domain united link adaptation technique to optimize link availability and resource utilization.